The Usborne Internet-linked ancient world - Chandler, Fiona; Usborne Publishing Ltd. (London : Usborne, 2004)
An illustrated description of ancient life-styles and cultures.
Includes index.
Spine title: Internet-linked ancient world.
Keywords: History, Ancient -- Juvenile literature; Ancient history